2005
DOI: 10.1017/s002211200500621x
|View full text |Cite
|
Sign up to set email alerts
|

Spreading characteristics of an insoluble surfactant film on a thin liquid layer: comparison between theory and experiment

Abstract: We describe measurements of the surface slope and reconstruction of the interface shape during the spreading of an oleic acid film on the surface of a thin aqueous glycerol mixture. This experimental system closely mimics the behaviour of an insoluble surfactant film driven to spread on a thin viscous layer under the action of a tangential (Marangoni) surface stress. Refracted image Moiré topography is used to monitor the evolution of the surface slope over macroscopic distances, from which the time variant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 38 publications
9
54
0
Order By: Relevance
“…17,29 Historically, most theoretical and experimental studies of Marangoni-driven spreading have focused on the air-liquid interface. 1,2, 5,7,8,11,[13][14][15][16][17][18][19][20][21][22][23]25 Comparatively few studies address other configurations such as the spreading of a fluids on solid substrates 30,31 and porous substrates. 32 So far no systematic studies on the spreading kinetics along the interface between immiscible liquids have been reported in literature.…”
Section: A Marangoni-driven Spreading On Deep Fluid Layersmentioning
confidence: 99%
See 3 more Smart Citations
“…17,29 Historically, most theoretical and experimental studies of Marangoni-driven spreading have focused on the air-liquid interface. 1,2, 5,7,8,11,[13][14][15][16][17][18][19][20][21][22][23]25 Comparatively few studies address other configurations such as the spreading of a fluids on solid substrates 30,31 and porous substrates. 32 So far no systematic studies on the spreading kinetics along the interface between immiscible liquids have been reported in literature.…”
Section: A Marangoni-driven Spreading On Deep Fluid Layersmentioning
confidence: 99%
“…In order to determine the power n, radial positions of the leading edge r i are measured at times t i typically over at least 1 decade in t. 8,25 In most of the experimental studies reported in literature, t i are within the range of 10 −2 -10 3 s and normal consumer video cameras can be used to record experiments. There are large similarities between the leading edge of a spreading film and the Reynolds ridge, a sharp transition in surface levels h between clean and contaminated surface areas of flowing water.…”
Section: B Detection Of the Leading Edgementioning
confidence: 99%
See 2 more Smart Citations
“…These forces can be generated by thermal [2,23], electrical [19], or chemical means [20]. Flows driven by Marangoni stresses have been found to yield interesting instabilities and new kinds of waves [2,5,14,21]. Chemical Marangoni stresses can be generated by the presence of surfactants (surface active agents), which typically decrease surface tension; nonuniform distributions of surfactant molecules creates such surface stresses [3,13,14].…”
Section: Introductionmentioning
confidence: 99%